TRANSPARENCY IN THE POLITICAL DECISION-MAKING PROCESS: ITS IMPACT ON PEOPLE'S WELFARE - Gunawan Widjaja (RADJA PUBLIKA, 2025)
This article highlights the importance of transparency as an essential component of a democratic and accountable political system. By increasing openness in decision-making processes, citizens gain better access to information necessary for active participation in democracy. Transparency helps reduce corruption and ensures that policies are implemented more fairly and in line with public needs. study The claims that with transparency, improvements in people's welfare can be achieved as policies are made based on clear information and strong participation from citizens. results The final show a positive relationship between transparency in political decision-making and improved quality of life.